Tissues and Cell Types of Appendage Regeneration: A Detailed Look at the Wound Epidermis and Its Specialized Forms - Aztekin, Can (Frontiers in Physiology, 2021)
Therapeutic implementation of human limb regeneration is a daring aim. Studying species that can regrow their lost appendages provides clues on how such a feat can be achieved in mammals. One of the unique features of regeneration-competent species lies in their ability to seal the amputation plane with a scar-free wound epithelium. Subsequently, this wound epithelium advances and becomes a specialized wound epidermis which is hypothesized to be the essential component of regenerative success. Recently, the wound epidermis and specialized wound epidermis terminologies have been used interchangeably. However, these tissues were historically separated, and contemporary limb regeneration studies have provided critical new information which allows us to distinguish them. Here, I will summarize tissue-level observations and recently identified cell types of wound epidermis and their specialized forms in different regeneration models.